MAKING CHANGE VISIBLE: HOW DIGITAL DEXTERITY BUILDS ADAPTIVE CAPACITY THROUGH VISUAL STRATEGY IN MSMEs E-COMMERCE - Gracela Marisa Sanapang; Bilyan Putra Sari; Muh Syulhasbiullah (RADJA PUBLIKA, 2026)
Set within Indonesia’s rapidly evolving platform-mediated commerce, this study explains how digital dexterity is converted into market-recognized adaptive capacity by specifying visual strategy as the execution mechanism at the customer interface. Drawing on dynamic capabilities and contemporary branding scholarship, we surveyed 240 e-commerce Micro, Small, And Medium Enterprise (MSMEs) entrepreneurs and estimated a theory-driven model using partial least squares structural equation modeling with validated reflective measures. The results are clear and internally consistent. Digital dexterity strengthens visual strategy. Digital dexterity also enhances adaptive capacity directly. Visual strategy improves adaptive capacity. Visual strategy further serves as a substantive conduit that links digital dexterity to adaptive capacity, indicating that digital skills matter most when institutionalized through a disciplined, cross-channel visual system that standardizes identity elements, reusable templates, and trust-bearing cues so strategic shifts become legible, credible, and repeatable. The study contributes an integrated account that connects digital transformation capability to adaptive outcomes through visual execution. Practically, we recommend building dexterity micro skills in analytics and rapid testing, codifying lightweight brand kits and creative templates, and instituting a regular creative review cadence so adjustments are communicated consistently across touchpoints. We also outline directions for longitudinal and platform-specific replications that pair perceptual data with behavioral performance traces.